REBRANDING SEBAGAI MANIFESTASI REFORMASI BIROKRASI ERA NEW NORMAL : PERSPEKTIF DIGITAL ERA GOVERNANCE - Yuliatris Yuliatris Mamuko (Badan Kepegawaian Negara | The National Civil Service Agency, 2021)
This article aims to explain how the BKKBN as a government agency carried out bureaucratic reform in the era of digital governance which was studied using the concept of Digital Weberianism Bureaucracy (DWB), specifically that took place during the Covid-19 pandemic. The DWB concept was introduced by Muellerleile and Robertson (1983) who argued that the form of efficiency, objectivity, and rationality of the Weberian bureaucracy had metamorphosed into a new, less visible but much stronger form of being a digital bureaucracy. This research was conducted using social media supported by interviews as a source of information to reveal the actors who played a role in the BKKBN rebranding program. With the mix method approach, it is expected to produce a strategy for optimizing the BKKBN rebranding strategy. The data obtained were analyzed using interactive analysis by Miles & Huberman (1992) and the mapping of actors was analyzed using the Social Network Analysis (SNA) approach with the help of Gephi software. This research was conducted to contribute to policy makers in the era of digital governance and to make theoretical and practical contributions related to the DWB concept in the digital era